A randomized, noninferiority, controlled trial of two doses of intravenous subdissociative ketamine for analgesia in the emergency department. (16th February 2021) - Lovett, Shannon; Reed, Trent; Riggs, Robert; Lew, George; Koch, Erica; Durazo‐Arvizu, Ramon A.; Rech, Megan A.
Abstract: Objective: This study aimed to determine if 0.15 mg/kg intravenous (IV) subdissociative ketamine is noninferior to 0.3 mg/kg in emergency department (ED) patients with acute pain. Methods: This randomized, prospective, double‐blinded, noninferiority trial included patients' age 18 to 59 years presenting to the ED with acute moderate to severe pain. Subjects were randomized to IV subdissociative ketamine, 0.15 mg/kg ("low" dose) or 0.30 mg/kg ("high" dose), over 15 minutes. The primary endpoint was the 11‐point numeric rating scale (NRS) pain score between groups at 30 minutes. Secondary endpoints included NRS pain scores at 15 and 60 minutes; change in NRS at 15, 30, and 60 minutes; rescue analgesia; and adverse effects. The noninferiority limit, δ 0, was set to 1.3. Results: Forty‐nine patients were included in each group. After the differences in the baseline NRS score were adjusted for, the mean NRS score at 30 minutes was 4.7 (95% confidence interval [CI] = 3.8 to 5.5) in the low‐dose group and 5.0 (95% CI = 4.2 to 5.8) in the high‐dose group (mean difference = 0.4, 95% CI = −0.8 to 1.5), indicating that the low‐dose subdissociative ketamine was noninferior to the high dose (lower limit of 95% CI = –0.8 to ≥1.3 = – δ 0 ). Adverse effects were similar at 30 minutes. At 15 minutes, the high‐dose group experienced greater change in NRS; however, more adverse effects occurred. Conclusion: Our data did not detect a large difference in analgesia or adverse effect profile between 0.15 mg/kg IV ketamine and 0.30 mg/kg in the short‐term treatment of acute pain in the ED.